Assessing the Feasibility of Providing a Parenting Intervention for War-Affected Families in Northern Uganda. Issue 3 (July 2015) - Wieling, Elizabeth; Mehus, Christopher; Möllerherm, Julia; Neuner, Frank; Achan, Laura; Catani, Claudia
Abstract : This article reports the results of a feasibility study of an intervention, Enhancing Family Connection (EFC), conducted in Northern Uganda in 2012. Enhancing Family Connection's sessions were an adaption of the Parent Management Training, Oregon model. Three interrelated areas of feasibility were assessed: ( a ) acceptability, ( b ) usability, and ( c ) limited efficacy. This study utilized questionnaires and semi-structured interviews completed by mothers and a focal child pre- and post-intervention. Results indicated that mothers found the intervention acceptable to their families and culture and showed promise for Enhancing Family Connection's efficacy in changing parenting behaviors. This study supports continued development of this intervention.